Self-Adjusting Monitor for Measuring Aging Rate and Advancement - Sadeghi-Kohan, Somayeh; Kamal, Mehdi; Navabi, Zainalabedin (IEEE Transactions on Emerging Topics in Computing)
Time-variant age information of different parts of a system can be used for system-level performance improvement through high-level task scheduling, thus extending the life-time of the system. Progressive age information should provide the age state that the system is in, and the rate that it is being aged at. In this paper, we propose a structure that monitors certain paths of a circuit and detects its gradual age growth, and provides the aging rate and aging state of the circuit. The proposed monitors are placed on a selected set of nodes that represent a timing bottleneck of the system. These monitors sample expected data on these nodes, and compare them with the expected values. The timing of sampling changes as the circuit ages and its delay increases. The timing of sampling will provide a measure of aging advancement of a circuit. To assess the efficacy of the proposed method and compare it with other state-of-the-art aging monitors, we use them on selected nodes of the execution unit of different processors, as well as some circuits from ITC99 benchmarks. The results reveal that the precision of our proposed method is between 0.12 (ns) to 0.401 (ns). Its Area and power overhead are negligible and are about 2.13 and 0.69 percent respectively.
Keywords: Age advancement; age monitoring clock; aging rate; self-adjusting monitors

Ecr 2.0: A Modular Framework for Evolutionary Computation in R - Bossek, Jakob (Proceedings of the Genetic and Evolutionary Computation Conference Companion)
The novel R package ecr (version 2), short for Evolutionary Computation in R, provides a comprehensive collection of building blocks for constructing powerful evolutionary algorithms for single- and multi-objective continuous and combinatorial optimization problems. It allows to solve standard optimization tasks with few lines of code using a black-box approach. Moreover, rapid prototyping of non-standard ideas is possible via an explicit, white-box approach. This paper describes the design principles of the package and gives some introductory examples on how to use the package in practise.
Keywords: evolutionary optimization; software-tools

A Pareto-Beneficial Sub-Tree Mutation for the Multi-Criteria Minimum Spanning Tree Problem - Bossek, Jakob; Grimme, Christian (2017 IEEE Symposium Series on Computational Intelligence (SSCI))
While finding minimum-cost spanning trees (MST) in undirected graphs is solvable in polynomial time, the multi-criteria minimum spanning tree problem (mcMST) is NP-hard. Interestingly, the mcMST problem has not been in focus of evolutionary computation research for a long period of time, although, its relevance for real world problems is easy to see. The available and most notable approaches by Zhou and Gen as well as by Knowles and Corne concentrate on solution encoding and on fairly dated selection mechanisms. In this work, we revisit the mcMST and focus on the mutation operators as exploratory components of evolutionary algorithms neglected so far. We investigate optimal solution characteristics to discuss current mutation strategies, identify shortcomings of these operators, and propose a sub-tree based operator which offers what we term Pareto-beneficial behavior: ensuring convergence and diversity at the same time. The operator is empirically evaluated inside modern standard evolutionary meta-heuristics for multi-criteria optimization and compared to hitherto applied mutation operators in the context of mcMST.
Keywords: Convergence; Encoding; Euclidean distance; Evolutionary computation; Heating systems; Optimization; Standards

Reliable Manufacturing of Heavy Copper Wire Bonds Using Online Parameter Adaptation - Meyer , Tobias; Unger, Andreas; Althoff, Simon; Sextro, Walter; Brökelmann, Michael; Hunstig, Matthias; Guth, Karsten (IEEE 66th Electronic Components and Technology Conference)
Usage of copper wire bonds allows to push power boundaries imposed by aluminum wire bonds. Copper allows higher electrical, thermal and mechanical loads than aluminum, which currently is the most commonly used material in heavy wire bonding. This is the main driving factor for increased usage of copper in high power applications such as wind turbines, locomotives or electric vehicles. At the same time, usage of copper also increases tool wear and reduces the range of parameter values for a stable process, making the process more challenging. To overcome these drawbacks, parameter adaptation at runtime using self-optimization is desired. A self-optimizing system is based on system objectives that evaluate and quantify system performance. System parameters can be changed at runtime such that pre-selected objective values are reached. For adaptation of bond process parameters, model-based self-optimization is employed. Since it is based on a model of the system, the bond process was modeled. In addition to static model parameters such as wire and substrate material properties and vibration characteristics of transducer and tool, variable model inputs are process parameters. Main simulation result is bonded area in the wiresubstrate contact. This model is then used to find valid and optimal working points before operation. The working point is composed of normal force and ultrasonic voltage trajectories, which are usually determined experimentally. Instead, multiobjective optimalization is used to compute trajectories that simultaneously optimize bond quality, process duration, tool wear and probability of tool-substrate contacts. The values of these objectives are computed using the process model. At runtime, selection among pre-determined optimal working points is sufficient to prioritize individual objectives. This way, the computationally expensive process of numerically solving a multiobjective optimal control problem and the demanding high speed bonding process are separated. To evaluate to what extent the pre-defined goals of self-optimization are met, an offthe- shelf heavy wire bonding machine was modified to allow for parameter adaptation and for transmitting of measurement data at runtime. This data is received by an external computer system and evaluated to select a new working point. Then, new process parameters are sent to the modified bonding machine for use for subsequent bonds. With these components, a full self-optimizing system has been implemented.
Keywords: Self-optimization; adaptive system; bond process; copper wire

Understanding Characteristics of Evolved Instances for State-of-the-Art Inexact TSP Solvers with Maximum Performance Difference - Bossek, Jakob; Trautmann, Heike (Proceedings of the XV International Conference of the Italian Association for Artificial Intelligence on Advances in Artificial Intelligence - Volume 10037)
State of the Art inexact solvers of the NP-hard Traveling Salesperson Problem TSP are known to mostly yield high-quality solutions in reasonable computation times. With the purpose of understanding different levels of instance difficulties, instances for the current State of the Art heuristic TSP solvers LKH+restart and EAX+restart are presented which are evolved using a sophisticated evolutionary algorithm. More specifically, the performance differences of the respective solvers are maximized resulting in instances which are easier to solve for one solver and much more difficult for the other. Focusing on both optimization directions, instance features are identified which characterize both types of instances and increase the understanding of solver performance differences.
Keywords: Combinatorial optimization; Instance hardness; Metaheuristics; Transportation; TSP

Self-Aware and Self-Expressive Systems – Guest Editor's Introduction - Torresen, Jim; Plessl, Christian; Yao, Xin (IEEE Computer)
Keywords: self-awareness; self-expression

The Value of Self-Service: Long-Term Effects of Technology-Based Self-Service Usage on Customer Retention. - Scherer, Anne; Wünderlich, Nancy; Von Wangenheim, Florian (MIS Quarterly)
Advancements in information technology have changed the way customers experience a service encounter and their relationship with service providers. Especially technology-based self-service channels have found their way into the 21st century service economy. While research embraces these channels for their cost-efficiency, it has not examined whether a shift from personal to self-service affects customer–firm relationships. Drawing from the service-dominant logic and its central concept of value-in-context, we discuss customers’ value creation in self-service and personal service channels and examine the long-term impact of these channels on customer retention. Using longitudinal customer data, we investigate how the ratio of self-service versus personal service use influences customer defection over time. Our findings suggest that the ratio of self-service to personal service used affects customer defection in a U-shaped manner, with intermediate levels of both self-service and personal service use being associated with the lowest likelihood of defection. We also find that this effect mitigates over time. We conclude that firms should not shift customers toward self-service channels completely, especially not at the beginning of a relationship. Our study underlines the importance of understanding when and how self-service technologies create valuable customer experiences and stresses the notion of actively managing customers’ cocreation of value.
Keywords: customer defection; customer retention; e-service; longitudinal; Self-service; value-in-context

A person-centred approach to students' transition into Higher Education - Brahm, Taiga; Wagner, Dietrich; Jenert, Tobias
A highly selective first study phase in many Swiss study programs leads to a rather competitive climate among students. However, the atmosphere at the university is an important factor for students' transition into Higher Education. An important question in this context is whether students' are equipped with different dispositions influencing how they cope with this transition. Other research has already shown that different groups of students can be identified regarding their student behavior. Yet, so far little is known about patterns of variables characterizing students, transitioning successfully. The paper takes advantage of a person-centered approach, i.e. the latent-class analysis, which makes it possible to identify groups of individuals, sharing common attributes. The research was conducted as a longitudinal study during their first year at a Swiss university. The return rate was about 67%, with 820 utilizable questionnaires at t1. Based on the analysis of students' anxiety, intrinsic motivation and self-efficacy, three distinct classes of students could be identified. The first class can be called the "highly motivated and self-confident" students. The second class is characterized by the same pattern, however, on a more intermediate level and the last class can be described as the "least motivated and most anxious" group of students. This study contributes to research and theory on students' transition into higher education and could be a first hint that students' experiences of this transition can vary substantially.
Keywords: Quantitative methods; Self-efficacy; Higher education; Motivation and Emotion

Kavitationsdetektion mittels Self-Sensing-Ultraschallwandler - Bornmann, Peter; Hemsel, Tobias; Sextro, Walter; Memoli, Gianluca; Hodnett, Mark; Zeqiri, Bajram (tm - Technisches Messen)
Eine Vielzahl von Prozessen in der Chemie und Verfahrenstechnik kann durch Ultraschall positiv beeinflusst werden. Oftmals ist ultraschallinduzierte Kavitation der Hauptwirkmechanismus für die positiven Effekte der Beschallung. Daher ist es notwendig die Kavitationsaktivität während des Prozesses zu quantifizieren um die Beschallung für den jeweiligen Prozess optimal gestalten und überwachen zu können. Eine Möglichkeit der prozessbegleitenden Kavitationsdetektion ist die Auswertung der akustischen Emissionen von oszillierenden und kollabierenden Kavitationsblasen mittels Drucksensoren in der Flüssigkeit. Raue Prozessrandbedingungen wie hohe Temperaturen oder aggressive Flüssigkeiten erschweren es jedoch geeignete Sensoren zu finden. Als Alternative wurde daher die Nutzbarkeit der Rückwirkung von Kavitationsereignissen auf das elektrische Eingansgssignal des Ultraschallwandlers zur Quantifizierung von Kavitation untersucht. Die experimentelle Analyse hat ergeben, dass das Einsetzen und in einigen Fällen auch die Art der Kavitation auf Basis der Rückwirkung auf das Stromsignal des Ultraschallwandlers bestimmt werden kann. Die Stärke der Kavitation war hingegen nicht aus den Stromsignalen abzuleiten.
Keywords: Kavitationsdetektion; Self-Sensing; So- nochemie; Ultraschallwandler

Advantages of reliability-adaptive system operation for maintenance planning - Meyer, Tobias; Kaul, Thorben; Sextro, Walter (Proceedings of the 9th IFAC Symposium on Fault Detection, Supervision and Safety for Technical Processes)
Intelligent mechatronic systems other the possibility to adapt system behavior to current dependability. This can be used to assure reliability by controlling system behavior to reach a pre-defined lifetime. By using such closed loop control, the margin of error of useful lifetime of an individual system is lowered. It is also possible to change the pre-defined lifetime during operation, by adapting system behavior to derate component usage. When planning maintenance actions, the remaining useful lifetime of each individual system has to be taken into account. Usually, stochastic properties of a fleet of systems are analyzed to create maintenance plans. Among these, the main factor is the probability of an individual system to last until maintenance. If condition-based maintenance is used, this is updated for each individual system using available information about its current state. By lowering the margin of error of useful lifetime, which directly corresponds to the time until maintenance, extended maintenance periods are made possible. Also using reliability-adaptive operation, a reversal of degradation driven maintenance planning is possible where a maintenance plan is setup not only according to system properties, but mainly to requirements imposed by maintenance personnel or infrastructure. Each system then adapts its behavior accordingly and fails according to the maintenance plan, making better use of maintenance personnel and system capabilities at the same time. In this contribution, the potential of maintenance plan driven system behavior adaptation is shown. A model including adaptation process and maintenance actions is simulated over full system lifetime to assess the advantages gained.
Keywords: Adaptive systems; Reliability analysis; Availability; Adaptive control; Maintenance; Self-optimizing systems; Self-optimizing control; Stochastic Petri-nets